Safety of parecoxib when used for more than 3 days for the management of postoperative pain. (September 2017) - Essex, Margaret Noyes; Cheung, Raymond; Li, Chunming; Xie, Li
Aim: To assess parecoxib safety when used for >3 days for postoperative pain management.Methods: Treatment-emergent adverse event (TEAE) occurrence after day 3 was examined in a pooled analysis of three placebo-controlled trials of parecoxib following general or gynecologic surgery, or total hip arthroplasty. A total of 358 patients received parecoxib, and 318 placebo.Results: Mean treatment duration was similar between treatment groups. The overall frequency of all TEAEs after day 3 was also similar between treatment groups. Most TEAEs occurred in <1% of patients after day 3; frequencies were similar between treatment groups. Most TEAEs were considered mild or moderate in severity.Conclusion: TEAE occurrence in patients receiving parecoxib for >3 days was low and similar to placebo after treatment day 3.